Polyphenols: Chemoprevention and therapeutic potentials in hematological malignancies - Izuegbuna, Ogochukwu O. (Frontiers in Nutrition, 2022)
Polyphenols are one of the largest plant-derived natural product and they play an important role in plants’ defense as well as in human health and disease. A number of them are pleiotropic molecules and have been shown to regulate signaling pathways, immune response and cell growth and proliferation which all play a role in cancer development. Hematological malignancies on the other hand, are cancers of the blood. While current therapies are efficacious, they are usually expensive and with unwanted side effects. Thus, the search for newer less toxic agents. Polyphenols have been reported to possess antineoplastic properties which include cell cycle arrest, and apoptosis via multiple mechanisms. They also have immunomodulatory activities where they enhance T cell activation and suppress regulatory T cells. They carry out these actions through such pathways as PI3K/Akt/mTOR and the kynurenine. They can also reverse cancer resistance to chemotherapy agents. In this review, i look at some of the molecular mechanism of action of polyphenols and their potential roles as therapeutic agents in hematological malignancies. Here i discuss their anti-proliferative and anti-neoplastic activities especially their abilities modulate signaling pathways as well as immune response in hematological malignancies. I also looked at clinical studies done mainly in the last 10–15 years on various polyphenol combination and how they enhance synergism. I recommend that further preclinical and clinical studies be carried out to ensure safety and efficacy before polyphenol therapies be officially moved to the clinics.